Jupiter's legacy. Volume 3 - Millar, Mark; Millar, Mark; Quitely, Frank, 1968- (Image Comics, Inc., 2020)
"Set one generation after the previous volume, America's superheroes have all had children, but can they ever fill their parents' shoes? More interested in celebrity and corporate sponsorship, the beautiful, twenty-something heroes of the modern era only want to be famous. However, worse is their political aspirations and a plan to take control away from a fallible and weak humanity."--Provided by publisher.